2021
DOI: 10.25259/sni_617_2021
|View full text |Cite
|
Sign up to set email alerts
|

Giant arachnoid cyst in adult presented with secondary epileptiform activity

Abstract: Background: Current studies contain controversies regarding indications and preferable surgical techniques for arachnoid cysts. Case Description: In this paper we present case report of giant arachnoid cyst of right frontal lobe in young left-handed adult with headache, MRI sings of brain compression and epileptiform activity on EEG, treated by microsurgical cystostomy. Conclusion: We add a case of young adult with tension headaches and possible sub-clinical seizures due to arachnoid cyst, whose symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Regarding the management of patients diagnosed incidentally, it is preferred to observe using serial MRIs, endocrinological tests, and a comprehensive ophthalmologic assessment and treated as per significant findings. As for the patients with symptoms, the treatment is surgical via cyst fenestration either by endoscopy or craniotomy [ 11 ]; surgical intervention should be reserved for those AC in which their size impacts their surroundings, whether it be via compression of neural structures, formations of hydrocephalus or symptomatic refractory presentations [ 4 ]. However, it has been reported that some patients were managed with medical treatment without the need to resort to surgical intervention [ 10 ]; our patient presented with frequent convulsions with CT finding of a large AC on imaging, so he was treated surgically via craniotomy due to the mass effect of the AC.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the management of patients diagnosed incidentally, it is preferred to observe using serial MRIs, endocrinological tests, and a comprehensive ophthalmologic assessment and treated as per significant findings. As for the patients with symptoms, the treatment is surgical via cyst fenestration either by endoscopy or craniotomy [ 11 ]; surgical intervention should be reserved for those AC in which their size impacts their surroundings, whether it be via compression of neural structures, formations of hydrocephalus or symptomatic refractory presentations [ 4 ]. However, it has been reported that some patients were managed with medical treatment without the need to resort to surgical intervention [ 10 ]; our patient presented with frequent convulsions with CT finding of a large AC on imaging, so he was treated surgically via craniotomy due to the mass effect of the AC.…”
Section: Discussionmentioning
confidence: 99%